Conductive rubber composite material
By grafting organic molecular chains on the surface of carbon nanotubes, the performance problems caused by the high fill number of parts in conductive rubber materials are solved, and the mechanical properties and flame retardant properties are improved, which significantly improves the application value of the materials.
Patent Information
- Application Number
- CN202411599058.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
The existing conductive rubber materials have problems such as high filling number, poor processing performance, reduced mechanical properties, and high costs, and the flame retardant effect is not ideal, which limits its application.
By grafting organic molecular chains through chemical bonding on the surface of carbon nanotubes, uniform dispersion of carbon nanotubes is achieved, the mechanical properties of rubber materials are improved, and stable and lasting flame retardant properties are given.
The mechanical properties of conductive rubber materials and significant improvements in flame retardant properties have been achieved, and better application value has been obtained.
Smart Images

Figure BDA0005127767150000031 
Figure BDA0005127767150000032 
Figure BDA0005127767150000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber composite materials, and in particular relates to a conductive rubber composite material. Background Art
[0002] Conductive rubber usually refers to a rubber with a volume resistance within 10 to the 9th ohm-cm. Since rubber is an excellent insulator, its volume resistance is greater than about 10 to the 14th. The principle is to add conductive carbon black, metal, and conductive reagents to the rubber to change the rubber's insulation. Conductive rubber is used in both military and commercial applications, and its main functions are sealing and electromagnetic shielding. Conductive rubber products can be molded or extruded, and are available in sheet or other punched shapes, with shielding performance up to 120dB (10GHz).
[0003] At present, the non-metallic fillers in conductive rubber mainly include carbonaceous particles such as carbon black, graphite, carbon fiber, graphene, and carbon nanotubes. Since such carbonaceous particles are inorganic fillers, if they are used as added fillers, not only will the added amount be high, which will make the processing performance and mechanical properties of the conductive rubber worse, but it will also be difficult to obtain ideal conductive properties. Moreover, they are easy to agglomerate, which restricts the conductive effect, and the cost is high.
[0004] In summary, the conductive rubber materials in the prior art have the problem of high filling ratio leading to poor processing performance, reduced mechanical properties and high cost. Secondly, the conductive rubber materials also have the problem of unsatisfactory flame retardant effect, which limits the application of conductive rubber materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a conductive rubber composite material.
[0006] The present invention grafts organic molecular chains on the surface of carbon nanotubes through chemical bonding through a series of chemical reactions, thereby achieving uniform dispersion of carbon nanotubes, improving the mechanical properties of rubber materials, and giving rubber materials safe, efficient, stable and long-lasting flame retardant properties.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A conductive rubber composite material, comprising the following raw materials in parts by weight: 50-60 parts of styrene-butadiene rubber, 20-30 parts of natural rubber, 20-30 parts of modified carbon nanotubes, 5-7 parts of zinc oxide, 2-3 parts of trioctyl trimellitate, 2-3 parts of antioxidant, 1.5-2 parts of stearic acid, 0.8-1.2 parts of tert-butyl perbenzoate, and 1.4-2 parts of sulfur;
[0009] The rubber composite material is prepared by the following method:
[0010] Add styrene-butadiene rubber and natural rubber into an internal mixer, set the temperature of the internal mixer to 130-140°C, and mix for 4-6 minutes, then add modified carbon nanotubes and zinc oxide, and continue mixing for 4-5 minutes, then add trioctyl trimellitate, tert-butyl perbenzoate and antioxidant, adjust the temperature to 145-155°C, continue mixing for 8-10 minutes, discharge the rubber, and produce a sheet to obtain a premixed sheet;
[0011] The premixed rubber sheet, sulfur and stearic acid are added into an internal mixer, the temperature is set to 110-120°C, the internal mixer is kneaded for 6-10 minutes, the rubber is discharged, and the mixture is cured to obtain a conductive rubber composite material.
[0012] Furthermore, the antioxidant is one of N-phenyl-α-aniline, N-phenyl-N'-isopropyl-p-phenylenediamine, N-N'-diphenyl-p-phenylenediamine, and antioxidant 4020.
[0013] Furthermore, the modified carbon nanotubes are prepared by the following steps:
[0014] S1, acidifying the carbon nanotubes with a strong acid to obtain carboxylated carbon nanotubes;
[0015] S2, add carboxyethylphenylphosphorous acid, triethylamine and anhydrous dichloromethane to a dry three-necked flask equipped with a stirring device, a condensing reflux device and a nitrogen conduit, introduce nitrogen, and continue to pass for 10 minutes, then add DMSO (dimethyl sulfoxide) solution of melamine and DIC (N, N-diisopropylcarbodiimide, dehydrating agent), after adding, stir and react for 3 hours at room temperature and under N2 protection, after the reaction is completed, extract three times with hot distilled water (temperature 60-70°C), take the organic layer, dry it over anhydrous magnesium sulfate, filter, and finally rotary evaporate (to remove dichloromethane) to obtain intermediate 1; the ratio of carboxyethylphenylphosphorous acid, triethylamine, anhydrous dichloromethane, melamine, and DIC is 0.1mol:10.1g:300mL:0.105mol:12.6g; the concentration of DMSO solution of melamine is 2.1mol / L;
[0016] Under the action of triethylamine and DIC, -COOH on the carboxyethylphenylphosphorous acid molecule undergoes an amidation reaction with -NH2 on the melamine molecule. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of melamine, under the influence of steric hindrance, only one -NH2 of melamine participates in the reaction to obtain intermediate 1. The reaction process is as follows:
[0017]
[0018] S3, intermediate 1 and THF (tetrahydrofuran) are placed in a three-necked flask, the temperature is maintained at 25-30 ℃, and stirred to mix them evenly; 4-chloro-1-butene, sodium carbonate and THF are mixed and then slowly dripped into the three-necked flask using a constant pressure dropping funnel, stirring while adding dropwise, and stirring and reacting for 3h under 25-30 ℃ after completion of the dropwise addition. After the reaction is completed, most of the THF is removed by rotary evaporation, distilled water is added to mix, and then extracted with ethyl acetate for multiple times, the organic phase is washed with saturated NaCl aqueous solution for multiple times and then dried with anhydrous Na2SO4, filtered, and finally distilled under reduced pressure to remove ethyl acetate to obtain intermediate 2; the ratio of the amount of intermediate 1, 4-chloro-1-butene and sodium carbonate is 33.8g:0.1mol:5.3g;
[0019] Under the action of sodium carbonate, -NH2 on the intermediate 1 molecule undergoes a nucleophilic substitution reaction with -Cl on the 4-chloro-1-butene molecule. By controlling the molar ratio of the two to be close to 1:1, a chemical reaction as shown below occurs to obtain intermediate 2:
[0020]
[0021] S4, mixing the intermediate 2 with a mixed solvent, then adding EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and NHS (N-hydroxysuccinimide), fully shaking to dissolve, to obtain a reaction solution; dispersing the carboxylated carbon nanotubes in the reaction solution according to a solid-liquid ratio of 1g:10mL, stirring the reaction in a constant temperature water bath at 50-55°C for 6h, centrifuging, and washing with deionized water 4-5 times, and finally fully drying in a vacuum oven at 60°C to obtain pre-modified carbon nanotubes; the ratio of the amount of intermediate 2, mixed solvent, EDC, and NHS is 37.6g:60mL:0.96g:0.58g; the mixed solvent is DMF (N,N-dimethylformamide) and MES buffer solution (concentration of 50mmol / L) mixed in a volume ratio of 2:1;
[0022] Under the action of EDC and NHS, -COOH on the surface of carboxylated carbon nanotubes undergoes amidation reaction with -NH2 on the intermediate 2 molecule to obtain intermediate 1. The specific reaction process is as follows:
[0023]
[0024] S5. Dissolve 4-chloro-1-butene in DMF in a dry three-necked flask equipped with a stirring device, add sodium carbonate, stir and dissolve evenly, place in a 30°C water bath, wait until the temperature is stable at 25-30°C, use a constant pressure dropping funnel to slowly drop the DMF dispersion of pre-modified carbon nanotubes into the flask, stir while adding, continue to stir and react at 25-30°C for 3h after the addition is complete, centrifuge and wash with deionized water 4-5 times, and finally fully dry in a 60°C vacuum oven to obtain modified carbon nanotubes; the DMF dispersion of pre-modified carbon nanotubes is prepared by ultrasonically dispersing pre-modified carbon nanotubes and DMF at a solid-liquid ratio of 1g:10mL; the mass ratio of 4-chloro-1-butene, sodium carbonate and pre-modified carbon nanotubes is 9g:5.3g:10g;
[0025]
[0026] The above process uses a series of chemical reactions to graft organic molecular chains on the surface of carbon nanotubes through chemical bonding. On the one hand, an organic layer can be formed on the surface of carbon nanotubes through the grafting of multiple organic molecular chains. Therefore, the interfacial compatibility between carbon nanotubes and rubber matrix can be effectively improved, and the uniform dispersion of carbon nanotubes can be promoted. On the other hand, the organic molecular chains grafted on the surface contain aliphatic carbon chains and multiple unsaturated carbon-carbon double bonds. The aliphatic carbon chains can further improve the compatibility of carbon nanotubes and rubber matrix and further promote dispersion. The unsaturated carbon-carbon double bonds can participate in the repolymerization process during the melt mixing process. Therefore, they can produce chemical bonding with the matrix and improve the molecular chain crosslinking of the matrix. The degree of bonding can be increased, thereby improving the mechanical strength of the matrix; in addition, it should be further explained that the grafted organic molecular chain also contains a nitrogen-containing six-membered ring, a phosphate group and a benzene ring. The nitrogen-containing six-membered ring belongs to the N series flame retardant component, and the phosphate group belongs to the P series flame retardant component, and the two together have a PN synergistic flame retardant effect. As the carbon nanotubes are uniformly dispersed in the rubber, the modified carbon nanotubes can give the rubber material safe, efficient, stable and long-lasting flame retardant properties; and the benzene ring belongs to a rigid group, which can also improve the mechanical strength of the rubber to a certain extent; finally, through the modification of the carbon nanotubes, the carbon nanotubes can be uniformly dispersed, the mechanical properties of the rubber material can be improved, and the rubber material can be given safe, efficient, stable and long-lasting flame retardant properties.
[0027] Furthermore, the specific process of step S1 is as follows:
[0028] The carbon nanotubes are placed in a conical flask, and then a strong acid is added, and ultrasonic treatment is performed in a water bath at 50° C. for 6 hours. After the mixture is cooled to room temperature, deionized water is added for dilution, centrifugation is performed, and the mixture is washed with ethanol and deionized water for 3-4 times in sequence, and finally dried in a vacuum oven at 60° C. to constant weight, and ground through a 200-mesh sieve to obtain carboxylated carbon nanotubes; the strong acid is a mixture of 98% by mass concentrated sulfuric acid and 37.5% by mass concentrated hydrochloric acid in a volume ratio of 5:1; the ratio of the carbon nanotubes to the strong acid is 1 g:12 mL;
[0029] By subjecting carbon nanotubes to ultrasonic shearing and oxidation treatment with strong acid, active carboxyl groups and hydroxyl groups can be introduced onto the surface of carbon nanotubes, thus laying the foundation for reaction sites for subsequent modification processes.
[0030] Beneficial effects of the present invention:
[0031] The present invention uses a series of chemical reactions to graft organic molecular chains on the surface of carbon nanotubes through chemical bonding, thereby achieving uniform dispersion of the carbon nanotubes, improving the mechanical properties of the rubber material, and giving the rubber material safe, efficient, stable and long-lasting flame retardant properties. The obtained conductive rubber material has extremely high application value. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] Preparation of modified carbon nanotubes:
[0035] S1. Place 10 g of carbon nanotubes in a conical flask, then add 120 mL of strong acid (100 mL of 98% by mass concentrated sulfuric acid and 20 mL of 37.5% by mass concentrated hydrochloric acid), and ultrasonically treat in a 50°C water bath for 6 h. After the mixture is cooled to room temperature, add 300 mL of deionized water to dilute, centrifuge, and wash with ethanol and deionized water three times in sequence. Finally, dry in a vacuum oven at 60°C to constant weight, grind through a 200-mesh sieve to obtain carboxylated carbon nanotubes.
[0036] S2, to a dry three-necked flask equipped with a stirring device, a condensing reflux device and a nitrogen conduit, 0.1 mol of carboxyethylphenylphosphorous acid, 10.1 g of triethylamine and 300 mL of anhydrous dichloromethane were added, nitrogen was introduced, and nitrogen was continuously introduced for 10 min, and then 50 mL of DMSO solution of melamine (concentration of 2.1 mol / L) and 12.6 g of DIC were added. After the addition, the mixture was stirred at room temperature and under N2 protection for 3 h. After the reaction was completed, it was extracted three times with hot distilled water (temperature 60° C.), the organic layer was taken, dried over anhydrous magnesium sulfate, filtered, and finally rotary evaporated (to remove dichloromethane) to obtain intermediate 1;
[0037] S3, 33.8g of intermediate 1 and 150mL of THF were placed in a three-necked flask, the temperature was maintained at 25-30°C, and the mixture was stirred to mix evenly; 0.1mol of 4-chloro-1-butene, 5.3g of sodium carbonate and 50mL of THF were mixed and then slowly dripped into the three-necked flask using a constant pressure dropping funnel, and stirred while adding dropwise. After the addition was completed, stirring and reacting at 25°C for 3h, most of the THF was removed by rotary evaporation, 200mL of distilled water was added and mixed, and then the mixture was extracted with ethyl acetate for several times, the organic phase was washed with a saturated NaCl aqueous solution for several times, and then dried with anhydrous Na2SO4, filtered, and finally distilled under reduced pressure to remove ethyl acetate to obtain intermediate 2;
[0038] S4, 37.6g of intermediate 2 was mixed with 60mL of a mixed solvent (40mL of DMF and 20mL of a 50mmol / L MES buffer solution), and then 0.96g of EDC and 0.58g of NHS were added, and the mixture was fully shaken to dissolve to obtain a reaction solution; 10g of carboxylated carbon nanotubes were dispersed in 100mL of the reaction solution, stirred in a 50°C constant temperature water bath for 6h, centrifuged, washed with deionized water 4 times, and finally fully dried in a 60°C vacuum oven to obtain pre-modified carbon nanotubes;
[0039] S5. In a dry three-necked flask equipped with a stirring device, 9 g of 4-chloro-1-butene was dissolved in 100 mL of DMF, and 5.3 g of sodium carbonate was added. After stirring and dissolving evenly, the mixture was placed in a 30°C water bath. When the temperature stabilized at 25°C, 100 mL of DMF dispersion of pre-modified carbon nanotubes (10 g of pre-modified carbon nanotubes and 100 mL of DMF were ultrasonically dispersed) was slowly dripped into the flask using a constant pressure dropping funnel. Stirring was continued while dropping. After the addition was completed, stirring was continued at 25°C for 3 hours. After the reaction was completed, the mixture was centrifuged and washed 4 times with deionized water. Finally, the mixture was fully dried in a vacuum oven at 60°C to obtain modified carbon nanotubes.
[0040] Example 2
[0041] Preparation of modified carbon nanotubes:
[0042] S1. Place 20 g of carbon nanotubes in a conical flask, then add 2400 mL of strong acid (200 mL of 98% by mass concentrated sulfuric acid and 40 mL of 37.5% by mass concentrated hydrochloric acid), and ultrasonically treat in a 50°C water bath for 6 h. After the mixture is cooled to room temperature, add 600 mL of deionized water to dilute, centrifuge, and wash with ethanol and deionized water for 4 times in sequence. Finally, dry in a vacuum oven at 60°C to constant weight, grind through a 200-mesh sieve to obtain carboxylated carbon nanotubes.
[0043] S2, to a dry three-necked flask equipped with a stirring device, a condensing reflux device and a nitrogen conduit, 0.2 mol of carboxyethylphenylphosphorous acid, 20.2 g of triethylamine and 600 mL of anhydrous dichloromethane were added, nitrogen was introduced, and nitrogen was continuously introduced for 10 min, and then 100 mL of DMSO solution of melamine (concentration of 2.1 mol / L) and 25.2 g of DIC were added. After the addition, the mixture was stirred at room temperature and under N2 protection for 3 h. After the reaction was completed, it was extracted three times with hot distilled water (temperature 70° C.), the organic layer was taken, dried over anhydrous magnesium sulfate, filtered, and finally rotary evaporated (to remove dichloromethane) to obtain intermediate 1;
[0044] S3, 67.6g of intermediate 1 and 300mL of THF were placed in a three-necked flask, the temperature was maintained at 30°C, and the mixture was stirred to mix evenly; 0.2mol of 4-chloro-1-butene, 10.6g of sodium carbonate and 100mL of THF were mixed and then slowly dripped into the three-necked flask using a constant pressure dropping funnel, and stirred while adding dropwise. After the addition was completed, stirring and reacting at 30°C for 3h, most of the THF was removed by rotary evaporation, 400mL of distilled water was added and mixed, and then the mixture was extracted with ethyl acetate for several times, the organic phase was washed with a saturated NaCl aqueous solution for several times, and then dried over anhydrous Na2SO4, filtered, and finally distilled under reduced pressure to remove ethyl acetate to obtain intermediate 2;
[0045] S4, 75.2g of intermediate 2 was mixed with 120mL of a mixed solvent (80mL of DMF and 40mL of a 50mmol / L MES buffer solution), and then 1.92g of EDC and 1.16g of NHS were added, and the mixture was fully shaken to dissolve to obtain a reaction solution; 20g of carboxylated carbon nanotubes were dispersed in 200mL of the reaction solution, stirred in a 55°C constant temperature water bath for 6h, centrifuged, washed with deionized water for 5 times, and finally fully dried in a 60°C vacuum oven to obtain pre-modified carbon nanotubes;
[0046] S5. In a dry three-necked flask equipped with a stirring device, dissolve 18 g of 4-chloro-1-butene in 200 mL of DMF, and add 10.6 g of sodium carbonate. After stirring and dissolving evenly, place it in a 30°C water bath. When the temperature stabilizes at 30°C, use a constant pressure dropping funnel to slowly drop 200 mL of DMF dispersion of pre-modified carbon nanotubes (20 g of pre-modified carbon nanotubes and 200 mL of DMF ultrasonically dispersed) into the flask, stirring while adding. After the addition is completed, continue to stir and react at 30°C for 3 hours. After the reaction is completed, centrifuge and wash with deionized water 5 times. Finally, fully dry in a 60°C vacuum oven to obtain modified carbon nanotubes.
[0047] Example 3
[0048] A conductive rubber composite material, comprising the following raw materials in parts by weight: 50 parts of styrene-butadiene rubber, 20 parts of natural rubber, 20 parts of modified carbon nanotubes prepared in Example 1, 5 parts of zinc oxide, 2 parts of trioctyl trimellitate, 2 parts of N-phenyl-α-aniline, 1.5 parts of stearic acid, 0.8 parts of tert-butyl peroxybenzoate, and 1.4 parts of sulfur;
[0049] The rubber composite material is prepared by the following method:
[0050] Add styrene-butadiene rubber and natural rubber into an internal mixer, set the mixer temperature at 130°C, and mix for 4 minutes, then add modified carbon nanotubes and zinc oxide, and continue mixing for 4 minutes, then add trioctyl trimellitate, tert-butyl perbenzoate and N-phenyl-α-aniline, adjust the temperature to 145°C, and continue mixing for 8 minutes, discharge the rubber, and produce a sheet to obtain a premixed sheet;
[0051] The premixed rubber sheet, sulfur and stearic acid were added into an internal mixer, the temperature was set to 110°C, the internal mixer was mixed for 6 minutes, the rubber was discharged, and the mixture was cured to obtain a conductive rubber composite material.
[0052] Example 4
[0053] A conductive rubber composite material, comprising the following raw materials in parts by weight: 55 parts of styrene-butadiene rubber, 25 parts of natural rubber, 25 parts of modified carbon nanotubes prepared in Example 2, 6 parts of zinc oxide, 2.5 parts of trioctyl trimellitate, 2.5 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, 1.8 parts of stearic acid, 1.1 parts of tert-butyl peroxybenzoate, and 1.7 parts of sulfur;
[0054] The rubber composite material is prepared by the following method:
[0055] Add styrene-butadiene rubber and natural rubber into an internal mixer, set the temperature of the internal mixer to 135°C, and mix for 5 minutes, then add modified carbon nanotubes and zinc oxide, and continue mixing for 4.5 minutes, then add trioctyl trimellitate, tert-butyl perbenzoate and N-phenyl-N'-isopropyl-p-phenylenediamine, adjust the temperature to 150°C, and continue mixing for 9 minutes, discharge the rubber, and produce a sheet to obtain a premixed film;
[0056] The premixed rubber sheet, sulfur and stearic acid were added into an internal mixer, the temperature was set to 115°C, the internal mixer was kneaded for 8 minutes, the rubber was discharged, and the mixture was cured to obtain a conductive rubber composite material.
[0057] Example 5
[0058] A conductive rubber composite material, comprising the following raw materials in parts by weight: 60 parts of styrene-butadiene rubber, 30 parts of natural rubber, 30 parts of modified carbon nanotubes prepared in Example 1, 7 parts of zinc oxide, 3 parts of trioctyl trimellitate, 3 parts of N-N'-diphenyl-p-phenylenediamine, 2 parts of stearic acid, 1.2 parts of tert-butyl peroxybenzoate, and 2 parts of sulfur;
[0059] The rubber composite material is prepared by the following method:
[0060] Add styrene-butadiene rubber and natural rubber into an internal mixer, set the mixer temperature at 140°C, and mix for 6 minutes, then add modified carbon nanotubes and zinc oxide, and continue mixing for 5 minutes, then add trioctyl trimellitate, tert-butyl perbenzoate and N-N'-diphenyl-p-phenylenediamine, adjust the temperature to 155°C, and continue mixing for 10 minutes, discharge the rubber, and produce a sheet to obtain a premixed sheet;
[0061] The premixed rubber sheet, sulfur and stearic acid were added into an internal mixer, the temperature was set to 120°C, the internal mixer was mixed for 10 minutes, the rubber was discharged, and the mixture was cured to obtain a conductive rubber composite material.
[0062] Comparative Example
[0063] The modified carbon nanotubes in Example 3 are replaced with ordinary carbon nanotubes, and the other raw materials and preparation process remain unchanged to obtain a conductive rubber composite material.
[0064] The rubber composite materials obtained in Examples 3-5 and Comparative Examples were processed and cut into test samples, and the following performance tests were performed:
[0065] Test the tensile properties of rubber materials according to GB / T 528-1998;
[0066] Test the volume resistivity of rubber materials according to MIL-DTL-83528C;
[0067] Flame retardant grade tested according to UL94-V0 standard:
[0068] The measured results are shown in the following table:
[0069]
[0070]
[0071] It can be seen from the data in the above table that the rubber composite material obtained by the present invention has good mechanical properties, excellent electrical conductivity and flame retardant properties; combined with the data of the comparative example, it can be seen that after modification, the carbon nanotubes can not only significantly improve the electrical conductivity of the rubber material, but also improve the mechanical properties of the material to a certain extent.
[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0073] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A conductive rubber composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of styrene-butadiene rubber, 20-30 parts of natural rubber, 20-30 parts of modified carbon nanotubes, 5-7 parts of zinc oxide, 2-3 parts of trioctyl trimellitate, 2-3 parts of antioxidant, 1.5-2 parts of stearic acid, 0.8-1.2 parts of tert-butyl peroxybenzoate, and 1.4-2 parts of sulfur; Wherein, the modified carbon nanotubes are prepared by the following steps: S1, acidifying the carbon nanotubes with a strong acid to obtain carboxylated carbon nanotubes; S2, add carboxyethylphenylphosphorous acid, triethylamine and anhydrous dichloromethane to a dry three-necked flask equipped with a stirring device, a condensing reflux device and a nitrogen conduit, introduce nitrogen, and continue to introduce nitrogen for 10 minutes, then add DMSO solution of melamine and DIC, after adding, stir and react for 3 hours at room temperature under N2 protection, extract three times with hot distilled water after the reaction is completed, take the organic layer, dry it over anhydrous magnesium sulfate, filter, and finally rotary evaporate to obtain intermediate 1; S3, placing intermediate 1 and THF in a three-necked flask, maintaining the temperature at 25-30°C, and stirring to mix them evenly; mixing 4-chloro-1-butene, sodium carbonate and THF, and then slowly dripping them into the three-necked flask using a constant pressure dropping funnel, stirring while adding, and continuing to stir and react at 25-30°C for 3h after the addition is completed. After the reaction is completed, post-processing is performed to obtain intermediate 2; S4, mixing the intermediate 2 with a mixed solvent, adding EDC and NHS, and fully shaking to dissolve to obtain a reaction solution; dispersing the carboxylated carbon nanotubes in the reaction solution according to a solid-liquid ratio of 1g:10mL, stirring the reaction in a constant temperature water bath at 50-55°C for 6h, centrifuging, and washing with deionized water for 4-5 times, and finally fully drying in a vacuum oven at 60°C to obtain pre-modified carbon nanotubes; S5. Dissolve 4-chloro-1-butene in DMF in a dry three-necked flask equipped with a stirring device, and add sodium carbonate. After stirring and dissolving evenly, place it in a 30°C water bath. When the temperature stabilizes at 25-30°C, slowly drop the DMF dispersion of pre-modified carbon nanotubes into the flask while stirring. After the addition is completed, continue to stir and react at 25-30°C for 3 hours. After the reaction is completed, centrifuge and wash with deionized water 4-5 times, and finally dry it in a vacuum oven at 60°C to obtain modified carbon nanotubes.
2. The conductive rubber composite material according to claim 1, characterized in that: In step S2, the ratio of carboxyethylphenylphosphite, triethylamine, anhydrous dichloromethane, melamine and DIC is 0.1 mol:10.1 g:300 mL:0.105 mol:12.6 g; the concentration of melamine dissolved in DMSO is 2.1 mol / L.
3. The conductive rubber composite material according to claim 1, characterized in that: In step S3, the ratio of the amount of the intermediate 1, 4-chloro-1-butene and sodium carbonate used is 33.8 g:0.1 mol:5.3 g.
4. The conductive rubber composite material according to claim 1, characterized in that: In step S4, the ratio of the amount of intermediate 2, mixed solvent, EDC, and NHS is 37.6 g:60 mL:0.96 g:0.58 g; the mixed solvent is obtained by mixing DMF and MES buffer solution in a volume ratio of 2:
1.
5. The conductive rubber composite material according to claim 1, characterized in that: The DMF dispersion of pre-modified carbon nanotubes in step S5 is prepared by ultrasonically dispersing pre-modified carbon nanotubes and DMF at a solid-liquid ratio of 1 g:10 mL; the mass ratio of 4-chloro-1-butene, sodium carbonate and pre-modified carbon nanotubes is 9 g:5.3 g:10 g.
6. The conductive rubber composite material according to claim 1, characterized in that: The rubber composite material is prepared by the following method: Add styrene-butadiene rubber and natural rubber into an internal mixer, set the temperature of the internal mixer to 130-140°C, and mix for 4-6 minutes, then add modified carbon nanotubes and zinc oxide, and continue mixing for 4-5 minutes, then add trioctyl trimellitate, tert-butyl perbenzoate and antioxidant, adjust the temperature to 145-155°C, continue mixing for 8-10 minutes, discharge the rubber, and produce a sheet to obtain a premixed sheet; The premixed rubber sheet, sulfur and stearic acid are added into an internal mixer, the temperature is set to 110-120°C, the internal mixer is kneaded for 6-10 minutes, the rubber is discharged, and the mixture is cured to obtain a conductive rubber composite material.
7. The conductive rubber composite material according to claim 1, characterized in that: The antioxidant is one of N-phenyl-α-aniline, N-phenyl-N'-isopropyl-p-phenylenediamine, N-N'-diphenyl-p-phenylenediamine and antioxidant 4020.